Inside the Great Mirror - Feibleman, J.K. author. aut Link
228 p.
Keywords: physical realist heavily bverlaid with the interpretation afforded by linguistic analysis, so he changed, too. But at the time, which was approximately during the second decade of the twentieth century, they were no doubt very close in their views. Russell acknowledged the influence of Wittgenstein in several places in the 1918 lectures on logical atomism. Wittgenstein might not have written the Tractatus had Russell not given the lectures on logical atomism, or at least had he not maintained the views there expressed. Certainly it is true in a very large sense that the Tractatus may be interpreted as a commentary on the 1918 lectures of Russell. Wittgenstein certainly did not hear them but, as Russell said, the topics were discussed together; and the debt of the Tractatus to the views of the contents of the lectures is obvious. Since Wittgenstein was the pupil and Russell the teacher, we may assume, despite the mutual influence, that the greater effect was Russell's. There is no space in which to go into a thorough analysis of the predecessors of Wittgenstein and of the influences upon him. In addition, there is not sufficient data. One clue, however, we are given. One of his friends has informed us that Wittgenstein "did read and enjoy Plato" and "recognized congenial features" in his philosophical method 1, although, to be sure, Wittgenstein is not said to have been a great reader of philosophy.